Investigation of metal-polyelectrolyte complex toxicity - Karahan, Mesut; Mustafaeva, Zeynep; Koc, Rabia Cakir; Bagirova, Melahat; Allahverdiyev, Adil M. (SAGE PUBLICATIONS INC, 2014)
Water-soluble binary and ternary copper complexes of polyelectrolytes were synthesized, and the toxicity of these complexes was tested in mouse fibroblast cell line (L929) in vitro. Both the binary and ternary complexes were prepared at the ratio of 0.4 mole copper(II) ions per monomer of acrylic acid and 0.5 mole copper(II) ions per monomer of methyl vinyl ether maleic anhydride, furthermore at the ratio of 1 and 2 mole bovine serum albumin per mole of polyacrylic acid and poly(methyl vinyl ether-co-maleic anhydride), respectively. Compared to binary copper(II)-polyelectrolyte complexes, these ternary complexes have been determined to be of least toxicity.
Keywords: transition metal chemistry; toxicity; proteins; Polymer-metal complexes; polyelectrolyte; AMPHIPHILIC IMMUNOGENS; COPPER COMPLEX; CHITOSAN; ALBUMIN; CU(II); Public, Environmental & Occupational Health; Toxicology